Plausible occupational impact on familial Treacher-Collins syndrome: Dental findings and management - Namita Kalra; Rishi Tyagi; Amit Khatri; Puja Sabherwal; Padma Yangdol (Wolters Kluwer Medknow Publications, 2020)
Treacher-Collins syndrome (TCS) is a disorder of autosomal dominant inheritance commonly linked to the mutation of human gene TREACLE (Treacher-Collins-Franceschetti 1). It primarily affects the structures derived from the first and second brachial arches by leading to neuroepithelial cell apoptosis and failure of neural crest cell migration. TCS commonly presents with anomalies of zygoma, mandible, and ears with typical bird-like facies. The variation in severity is found to increase over generations and is affected by environmental factors and stochastic events. The paper presents a case of familial TCS in a mother and daughter with increased severity in the second generation; it also illustrates the correlation of occupational impact due to cumulative maternal exposure to polyvinyl acetate-based adhesive resin as an occupational hazard for over 30 years.